The Influence of Corporate Governance and Ownership Structure on Competitive Advantage: An Empirical Study in Indonesian Manufacturing Industry - Linggahua, Akhyian Hamimah; Nuzula, Nila Firdausi; Sugiastuti, Reika Happy (FIA UB, 2023)
Corporate governance describes the governance used to carry out the business activities of a corporation. This study aims to analyze the influence of Corporate Governance and Ownership Structure on Competitive Advantage. The Corporate Governance variable is explained by the size of the board of commissioners, educational background of the chairman of the board of commissioners, size of the board of directors, educational background of the chairman of the board of directors, and experience of the board of Directors. The competitive advantage variable is explained by capital intensity, market share, receivable turnover, cost of sales, and inventory turnover. This type of research is explanatory research because it explains the influence of corporate governance and ownership structure on competitive advantage. The relationship between variables is explained by testing two hypotheses. The sampling method used purposive sampling and obtained a sample of 36 companies, obtained from 12 companies for 3 years. using secondary data, namely the company's annual report. Data analysis in this study used Partial Least Square (PLS) with WarpPLS 7.0 software. The test results in this study indicate that there is a significant influence of corporate governance and ownership structure on competitive advantage.